Unintended evolutionary consequences of a minimum landing size regulations: Evidence and implications of fisheries-induced evolution - Airam Guerra-Marrero; Javier Baixauli-Rodríguez; Ana Espino-Ruano; David Jiménez-Alvarado; Lorena Couce-Montero; Ángelo Santana-Del Pino; José J. Castro (PLoS ONE, 2026)
A total of 725 historical photographs taken between 1940–2022 were analysed to assess the temporal variations in target species and the size-frequency distribution of recreational fishing catches in the Canary Islands. A significant shift from predominantly single-species fishing to a more diverse, multispecies approach was observed, particularly since 2000. Species such as Dentex gibbosus , Diplodus cadenati , Epinephelus marginatus , Lithognathus mormyrus , and Sparisoma cretense showed consistent size reductions over the decades. The analysis revealed discrepancies between current Minimum Landing Sizes (MLS) in the Canary Islands and the lengths at which these species reach sexual maturity (L50), or the length at which 50% of fish are mature. Except for Diplodus cadenati , the MLS for the examined species are smaller than their respective L50 values, indicating that individuals are often harvested before reproducing. The use of the L50 as a standard for reference length can trigger a fisheries-induced evolution. This occurs because the extractive activities resulting from this standard promote reduced fish size and earlier maturation, which could lead to lasting evolutionary changes in fish communities. Our study underscores the need to reevaluate minimum landing size (MLS) regulations and seek a transition towards L95, to ensure they are aligned with the reproductive biology of target species, thereby promoting sustainable fishing practices and the conservation of marine biodiversity in the Canary Islands. Even so, this proposed improvement and the results of this study should be combined with a Harvest-slot length limits (based on species-specific ecological and demographic studies) to ensure the survival of megaspawners.